Aksesibilitas Penyandang Disabilitas Terhadap Pelayanan Publik di Kota Surakarta - Lelly Nuraviva; Priyatno Harsasto; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2018)
ACCESSIBILITY OF PERSONS WITH DISABILITIESON PUBLIC FACILITIES IN SURAKARTA             The existence of Surakarta regulation number 2 year 2008 about difable equality, then shows that the Government of Surakarta has already committed to pay attention to persons with disabilities. In fact, however, it’s seen from the results of previous research that there still many public facilities that are not in accordance with the accessibility standard that is their right. The question is : how the success / failure from accessibility policy for persons with disabilities towards the provision of public facilities in Surakarta? What standard of success / failure about the accessibility policy in Surakarta? The purpose of this research is to explain the success / failure of the persons with disabilities accessibility policy to public facilities, and to explain couse of the success / failure of the persons with disabilities accessibility policy to public facilities.            The research was conducted using the theory of public service, persons with disabilities as citizens, accessibility as citizen’s right, and implementation of public policy. The method used in this research is qualitative method, data collecting method by using observation, interview, and documentation. In testing the validity and accuracy of data using triangulation technique of source and theory.            The result showed from regulation aspect, Government of Surakarta deserves to be appreciated to tried to fulfill the rights of people with disabilities as citizens by providing equality disabilities regulation. However, from implementation aspect, there needs an improvements because the accessibility for persons with disabilities runs optimally can be seens through public facilities condition in Surakarta. The existing of public facilities in Surakarta do not completely ignoring the accessibility guidance which means that there are public facilities that are good enough but more are not optimal due to lack of knowledge and understanding of state organizer as policy maker to the reference of accessibilities persons with disabilities. The lack of persons with disabilities understanding as citizen have more effect to their needs are neglecated. The low of their existance from the political side as a citizen to affect the regulation and even affecting the number during elections so that their involvement is ignorance by policy maker, the involvement of many parties lead to ineffectiveness in policy implementation. The existance of a non-specific budget causes unoptimal construction of public facilities, and the lack of coordination in the form of advocacy conducted by the Social Service with other agencies. Key words : Policy, Accessibility, People With Disabilities.